Tourism Website through Google Sites Development in Improving Students’ Writing Skill - Sumarsih Sumarsih; I Wayan Dirgeyasa; Rosdiana Siregar; Asrita Sari (Association of Language Teachers in Southeast Asia (ALTSA), 2023)
Teachers in the 21st century should assist all students in learning how to learn. Teachers are expected to inspire creativity, encourage cooperation, and educate the students how to communicate. The teachers are expected to create independent learning situation through utilizing digital media like google sites as one of free google products. As students of majoring in tourism are expected to promote tourism places globally by having English proficiency. In this digital era, writing can be an alternative to communicate everything via digital platform. Therefore, the study aimed to develop website on tourism through google sites in improving students’ writing skill. The study was conducted at SMK Negeri 1 Medan. ADDIE (Analysis, Design, development, implementation and evaluation) model was used in conducting the study. XI grade students of tourism major were involved in this study. Depth interview and distributing questionnaire were administered to gain data of the study. the data analysis was conducted to determine the validity and effectiveness of product. The findings of study showed that 90% of students really needed writing skill and wanted to develop their skill in digital platform like a website. Then, 10% of students hadn’t decided whether it was needed for the future after graduation or not. However, those students needed to learn and have the skill. After doing validating, website on tourism through google sites had been valid (93%) to be applied. It was also effective to improve students’ writing skill after analyzing the result of English test and response of teacher and students.